Mouse Metanephric Mesenchymal Cell–Derived Angioblasts Undergo Vasculogenesis in Three-Dimensional Culture - Patel, Mandakini (Am J Pathol, 2018)
In vitro models for the investigation of renal vascular development are limited. We previously showed that isolated metanephric mesenchymal (MM) and ureteric bud (UB) cells grown in three-dimensional (3D) matrices formed organoids that consisted of primitive vascular structures surrounding a polarized epithelium. Here, we examined the potential of two principal effectors of vasculogenesis, vascular endothelial growth factor A (VEGF-A), and platelet-derived growth factor B chain (PDGF-BB), to stimulate MM cell differentiation. The results showed that MM cells possess angioblast characteristics by expressing phenotypic markers for endothelial and mesenchymal cells. UB cells synthesize VEGF-A and PDGF-BB proteins and RNA, whereas the MM cells express the respective cognate receptors, supporting their role in directional induction of vasculogenesis. VEGF-A stimulated proliferation of MM cells in monolayer and in 3D sponges but did not affect MM cell migration, organization, or vasculogenesis. However, PDGF-BB stimulated MM cell proliferation, migration, and vasculogenesis in monolayer and organization of the cells into primitive capillary-like assemblies in 3D sea sponge scaffolds in vitro. A role for PDGF-BB in vasculogenesis in the 3D MM/UB co-culture system was validated by direct interference with PDGF-BB or PDGF receptor-β cell interactions to implicate PDGF-BB as a primary effector of MM cell vasculogenesis. Thus, MM cells resemble early renal angioblasts that may provide an ideal platform for the investigation of renal vasculogenesis in vitro.